Repetitive mTBI is associated with age-related reductions in cerebral blood flow but not cortical thickness. Issue 2 (February 2021) - Clark, Alexandra L; Weigand, Alexandra J; Bangen, Katherine J; Merritt, Victoria C; Bondi, Mark W; Delano-Wood, Lisa
Mild traumatic brain injury (mTBI) is a risk factor for Alzheimer's disease (AD), and evidence suggests cerebrovascular dysregulation initiates deleterious neurodegenerative cascades. We examined whether mTBI history alters cerebral blood flow (CBF) and cortical thickness in regions vulnerable to early AD-related changes. Seventy-four young to middle-aged Veterans (mean age = 34, range = 23–48) underwent brain scans. Participants were divided into: (1) Veteran Controls ( n  =   27), (2) 1–2 mTBIs ( n  =   26), and (2) 3+ mTBIs ( n  =   21) groups. Resting CBF was measured using MP-PCASL. T1 structural scans were processed with FreeSurfer. CBF and cortical thickness estimates were extracted from nine AD-vulnerable regions. Regression analyses examined whether mTBI moderated the association between age, CBF, and cortical thickness. Regressions adjusting for sex and posttraumatic stress revealed mTBI moderated the association between age and CBF of the precuneus as well as superior and inferior parietal cortices ( p's  < .05); increasing age was associated with lower CBF in the 3+ mTBIs group, but not in the VCs or 1–2 mTBIs groups. mTBI did not moderate associations between age and cortical thickness ( p's >.05). Repetitive mTBI is associated with cerebrovascular dysfunction in AD-vulnerable regions and may accelerate pathological aging trajectories.